Cultural mosaics, social structure, and identity: The Acheulean threshold in Europe. Issue 156 (July 2021) - Ashton, Nick; Davis, Rob
Abstract: The period between 600 and 400 ka is a critical phase for human evolution in Europe. The south and northwest saw a dramatic increase in sites, the spread of handaxe technology alongside bone and wooden tool manufacture, efficient hunting techniques, and the use of fire. Lithic assemblages show considerable variation, including the presence/absence of handaxes and tool morphology. To explain this variation, we propose the Cultural Mosaic Model, which suggests that there is a range of expressions of the Acheulean, with local resources being instrumental in creating distinct material cultures with or without handaxes. We argue that if typologically and technologically distinct assemblage types are regionally distributed, chronologically separated, and persistent over time, then they are unlikely to be caused purely by raw material constraints or functional variation but rather reflect populations with different material cultures. We initially assess the model using British data. Britain was a northwestern peninsula of Europe, and oscillations in climate led to episodic occupation. The terraces of the pre-MIS 12 Bytham River provide a framework for dating occupation to MIS 13 and 15, while during MIS 11, archaeological sites with rich environmental records can be dated to substage level. We suggest there are six chronologically and typologically distinct assemblage types that reflect a series of population incursions into Britain. We review the broader European lithic record, which is consistent with the Cultural Mosaic Model. In developing the model, we suggest that during stable climate, localized cultures developed, while climatic change led to shifts in population, with increased knowledge exchange and gene flow. We suggest that group expression through material culture was an important stage in social development by promoting group cohesion, larger group size, better cooperation, improved knowledge transfer, and enabling populations to survive in larger foraging territories in northern Europe. Highlights: Six phases of human occupation can be identified in Britain between 600 and 360 ka. Each phase has distinct lithic assemblages suggesting new populations from Europe. Variation in Europe shows a mosaic of cultural groups reflecting local circumstances. Distinctive material culture strengthens social cohesion and larger group size. Strong social cohesion is critical for more dispersed populations in northern Europe.